Angle Kamera Subjektif dalam Film “Aku Ada” - Latief Rakhman Hakim (Rekam: Jurnal Fotografi, Televisi, Animasi)
While watching a movie, the viewers sometimes are get involved to thescreen. The viewers can feel the emotion described in a scene. This is happened due to the projection and imaginary identification processes. The viewers feel as if they have taken part to the scene. However the viewers just passively involved, there is no interaction between the actors/characters and the viewers.A subjective camera angle is the way to invite the viewers to get involvedin the scenes of ‘Aku Ada’ movie. The viewers interact with the actors on that movie through an angle’s point of view variation. The viewers can change the specific actor’s point of view in watching some different events, objects and settings in a scene. Their point of view can also be moved from a certain actor to the other actors, but how if the viewers cannot identify themselves to the movie.This of course can destroy the narrative structure and blur the message delivered by the movie.The originality of the movie “Aku Ada” is to place the viewers to thescenes through a subjective camera angle on the overall shots, and suddenly move the point of view from a certain actor to the others. The viewers will in turn change in involving the act of one actor with the others. This changing of sudden point of view are not be done by the previous movies to be a reference. The application of subjective camera angle in the movie “Aku Ada” can built up the viewer’s interaction to the scenes on the movie. They can project themselves on the movie scenes and can identify themselves to be involved in the movie “Aku Ada” through interaction or eye-contact with the characters on the movie.